Effects of changing jaw height on F1 during babble: A case study at 9 months. - Steeve, Roger W. (Clinical Linguistics & Phonetics, 2012)
An empirical gap exists in our understanding of the extent that mandibular kinematics modulate acoustic changes in natural babble productions of infants. Data were recorded from a normal developing 9-month-old infant. Mandibular position was tracked from the infant during vowel and canonical babble. Linear predictive coding analysis was used to track estimates of formant center-frequency for F1. For each sample, a correlation coefficient was computed between changes in jaw height and formant history for F1. A Mann-Whitney rank sum test reached significance for differences among coefficients for vowel and canonical babble. Coefficients for vowel babble productions were nearest to −1 with a median of r  ==  − 0.76, showing the strongest relationship between jaw position and formant history, while the median for canonical babble coefficients was r  ==  − 0.54, indicating greater contribution of the tongue and lips. This 9-month-old infant exhibited plasticity for coordinating the jaw, tongue and lips among babble types.